KEEFEKTIFAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) BERBANTU MEDIA DIAGRAM BATANG TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 4 JELOBO KLATEN - Anisa Rona Soraya; A.Y. Soegeng Ysh; Mira Azizah (Jurnal Guru Kita PGSD, 2019)
Abstract: The Effectiveness of Team Assisted Individualization (TAI) Learning Model Assisted by a Media Bar Diagram Against Learning Outcomes of Mathematic for Class IV SDN 4 Jelobo Klaten Students. This study aims to determine the significant effectiveness of the application of the learning model of team assisted individualization assisted by the media of bar charts to the learning outcomes of Mathematic for grade IV SDN 4 Jelobo Klaten students. . This type of research is a quantitative study using a quasi experimental design with a form of non equivalent control group design. The population in this study were all students of class IV SDN 4 Jelobo Klaten, totaling 24 students and all students of class IV SDN 2 Teloyo Klaten, totaling 24 students. The data obtained were analyzed using t-test. Based on the analysis results obtained t_count = 3.106 with α = 5% and dk = 24 + 24 - 2 = 46 obtained t_table = 2.012. So t_count> t_table, that is 3.106> 2.012 then H0 is rejected and Ha is accepted, so that the Team Assisted Individualization learning model with the media bar chart is effective on learning outcomes of Mathematic. The average value of the experimental class students is 84.17 higher than the average value of the control class that is 76.00.Keywords: Team Assisted Individualization, learning outcomesAbstrak: Keefektifan Model Pembelajaran Team Assisted Individualization (TAI) Berbantu Media Diagram Batang Terhadap Hasil Belajar Matematika Siswa Kelas IV SDN 4 Jelobo Klaten. Penelitian ini bertujuan untuk mengetahui keefektifan yang signifikan pada penerapan model pembelajaran team assisted individualization berbantu media diagram batang terhadap hasil belajar Matematika siswa kelas IV SDN 4 Jelobo Klaten. . Jenis penelitian ini merupakan penelitian kuantitatif menggunakan desain quasi experimental dengan bentuk non equivalent control group design. Populasi dalam penelitian ini adalah seluruh siswa kelas IV SDN 4 Jelobo Klaten yang berjumlah 24 siswa dan seluruh siswa kelas IV SDN 2 Teloyo Klaten yang berjumlah 24 siswa. Data yang diperoleh dianalisis dengan menggunakan uji-t. Nilai rata-rata siswa kelas eksperimen yaitu 84,17 lebih tinggi daripada nilai rata-rata kelas kontrol yaitu 76,00.Kata Kunci: Team Assisted Individualization, hasil belajar.